Menimbang Dampak Pembubaran Komisi Aparatur Sipil Negara (KASN) Terhadap Netralitas ASN pada Pemilu 2024 - Kurniawan, Salma Nayla Ayunda; Salsabila, Tsabita Moeldi; Mahendra, Wahyu (Jurnal Ilmiah Wahana Pendidikan, 2024)
Supervision is an aspect that must be strengthened to maintain the meritocracy system in carrying out bureaucratic reform in government in Indonesia. One form of supervision within the scope of public institutions is the establishment of the State Civil Apparatus Commission (KASN) which is tasked with supervising the performance and integrity of ASN in carrying out their duties. However, the revision of Law Number 5 of 2014 concerning State Civil Apparatus has consequences for lax supervision of ASN. It is feared that ASN's neutrality will become a big issue in the 2024 political year. For this reason, this research discusses the possible impacts on ASN's neutrality in the 2024 elections if KASN is officially disbanded. This research was conducted using qualitative research methods with data reduction techniques, data presentation, and drawing conclusions. Based on the results of the analysis carried out, it was found that the possible impact was a decline in the quality of public services due to ASN's alignment with certain political interests, recruitment and position mapping in government institutions were influenced by corruption, collusion and nepotism. Then, there will be potential for commercialization of positions by ASN.